Microbial Iron Cycling in Acidic Geothermal Springs of Yellowstone National Park: Integrating Molecular Surveys, Geochemical Processes, and Isolation of Novel Fe-Active Microorganisms - Kozubal, Mark A.; Macur, Richard E.; Jay, Zack J.; Beam, Jake P.; Malfatti, Stephanie A.; Tringe, Susannah G.; Kocar, Benjamin D.; Borch, Thomas; Inskeep, William P. (Frontiers in Microbiology, 2012)
Geochemical, molecular, and physiological analyses of microbial isolates were combined to study the geomicrobiology of acidic iron oxide mats in Yellowstone National Park (YNP). Nineteen sampling locations from 11 geothermal springs were studied ranging in temperature from 53 to 84 °C and pH 2.4 to 3.6. All iron-oxide mats exhibited high diversity of crenarchaeal sequences from the Sulfolobales, Thermoproteales, and Desulfurococcales. The predominant Sulfolobales sequences were highly similar to Metallosphaera yellowstonensis str. MK1, previously isolated from one of these sites. Other groups of archaea were consistently associated with different types of iron oxide mats, including undescribed members of the phyla Thaumarchaeota and Euryarchaeota. Bacterial sequences were dominated by relatives of Hydrogenobaculum spp. above 65-70 °C, but increased in diversity below 60 °C. Cultivation of relevant iron-oxidizing and iron-reducing microbial isolates included Sulfolobus str. MK3, Sulfobacillus str. MK2, Acidicaldus str. MK6, and a new candidate genus in the Sulfolobales referred to as Sulfolobales str. MK5. Strains MK3 and MK5 are capable of oxidizing ferrous iron autotrophically, while strain MK2 oxidizes iron mixotrophically. Similar rates of iron oxidation were observed for M. yellowstonensis str. MK1 and Sulfolobales str. MK5 cultures, and these rates are close to those measured in situ. Biomineralized phases of ferric iron varied among cultures and field sites, and included ferric oxyhydroxides, K-jarosite, goethite, hematite, and scorodite depending on geochemical conditions. Strains MK5 and MK6 are capable of reducing ferric iron under anaerobic conditions with complex carbon sources. The combination of geochemical and molecular data as well as physiological observations of isolates suggests that the community structure of acidic Fe mats is linked with Fe cycling across temperatures ranging from 53 to 88 oC.